Market Structure, Income Diversity, and Stability: Empirical Study of Banking Industry Indonesia - Ganefi, Hadi Satria; Ermawati, Wita Juwita; Hakim, Dedi Budiman (Jurnal Keuangan dan Perbankan, 2021)
Banking as an intermediary institution has an essential role in the world of economy. Apart from providing financing to the real sector, banks currently still dominate the Indonesian financial system with an asset share of 77.25%. Based on the existing conditions, Indonesia's banking market is still dominated by several banks, especially in the BUKU 4 bank group. This is to indicate a bank of Indonesia is generally still facing relatively low competition. In addition, the large concentration makes it necessary for banks to divert their main activities by diversifying into non-traditional activities in carrying out their operations. This study aims to analyze how the market competition in Indonesia during the period 2014-2019 and examine the effect of competition and diversification income on stable banks. The panzer rosse model is used to analyze the market structure; for diversification, this research uses calculations with the Herfindahl Hirshman Index while stability uses two risk measures, namely NPL and Z Score, as a proxy for stability. The results show that, in general, the banking industry is under monopolistic competition. Competition has a significant effect on stability banks as measured through NPL risk, and this research supports the competition-fragility paradigm. A meanwhile, diversification income variables have not to effect on stability.DOI: 10.26905/jkdp.v25i3.5887